2010
DOI: 10.1017/s1742170510000384
|View full text |Cite
|
Sign up to set email alerts
|

Moving local food through conventional food system infrastructure: Value chain framework comparisons and insights

Abstract: There is growing recognition that the direct marketing initiatives favored by many local food activists and proponents often lack the capacity to meet rapidly expanding consumer demand for local food. To address these needs, some food systems researchers have identified a role for ‘transitional’ food systems that piggyback on the pre-existing, conventional local food system infrastructure, while moving toward the social and economic benefits of direct marketing. This paper uses a value chain model (based on bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(137 citation statements)
references
References 21 publications
2
120
0
3
Order By: Relevance
“…Regional producers are often dependent on "conventional" intermediaries in the food chain like wholesalers [4]. However, the use of conventional food system infrastructure might be helpful for the development of regional food chains and can take over a role in the transition process towards more regional food systems [38,61].…”
Section: Food Chain Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional producers are often dependent on "conventional" intermediaries in the food chain like wholesalers [4]. However, the use of conventional food system infrastructure might be helpful for the development of regional food chains and can take over a role in the transition process towards more regional food systems [38,61].…”
Section: Food Chain Organizationmentioning
confidence: 99%
“…Bloom and Hinrichs [38] and Ilbery and Maye [4] have clearly shown that many small-scale producers do not rely only on alternative or short chains, but also make use of conventional long chains. In addition, a recent German study into regional initiatives reveals hybrid strategies of food chain actors, who market conventional and organic produce through different channels, including direct marketing and conventional retail [113].…”
Section: Towards a Regional Organic Food Systemmentioning
confidence: 99%
“…Analyses of SMFE use of conventional food system infrastructure have been based on case studies at single points in time, typically over one year or one growing season, and rely on interviews and observational data (e.g., Abatekassa & Peterson, 2011;Bloom & Hinrichs, 2010, 2011Clark & Inwood, 2015,;McCallum, Campbell, & MacRae, 2014). These studies have identified the factors that constrain businesses operating at different scales from successfully engaging in market relationships.…”
Section: Introductionmentioning
confidence: 99%
“…The value chain model advanced by Stevenson and Pirog (2008) is helpful for understanding why. Derived to meet the unique challenges of local food chains operating at a larger scale, value chains distinguish themselves through four core dimensions: differentiating value-added products; committing to the welfare, particularly financial, of all participants; creating strategic partnerships; and creating trust and shared governance (Bloom & Hinrichs, 2011). By incorporating these key dimensions, successful value chains are able to "operate at a larger scale than direct marketing while deliberately embedding mechanisms to ensure social, environmental and economic benefits for supply chain participants" (Bloom & Hinrichs, 2011, p. 14).…”
Section: Discussionmentioning
confidence: 99%
“…Another concept potentially applicable to major retailer involvement in localization is that of transitional food system change: piggybacking on the dominant system to advance desirable changes in supply chains (Bloom & Hinrichs, 2011). This is part of the value chain approach (Stevenson & Pirog, 2008) that builds on some aspects of traditional supply chain analysis (such as scale and efficiency), but with the added dimension of values-based production and distribution (in this case localization and its potential benefits).…”
Section: Localization: a Review Of The Supply Chain Transformation LImentioning
confidence: 99%